A survey of household saving behavior in Japan - Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2007)
This paper presents data on Japan's household saving rate, considers the reasons for Japan's high household saving rate in the past and the reasons for the recent decline therein, projects future trends in Japan's household saving rate, and consider the implications of my findings. It finds that Japan's high household saving rate was a temporary phenomenon and that it was high in both absolute and relative terms during the 1955-95 period (especially during the 1960s and 1970s) but that it was not unusually high during the prewar and early postwar periods or after 1995; second, that Japan's temporarily high household saving rate was due not to culture but to temporary economic, demographic, and institutional factors; third, that the decline in Japan's household saving rate since the mid-1970s is due to the weakening of these factors and that Japan's household saving rate can be expected to decline even further as these factors become even less applicable and that the rapid aging of Japan's population has played the most important role; and fourth, that there is nothing to worry about even if Japan's household saving rate falls to zero or even negative levels.
Keywords: D12; D91; E21; 330; Household Saving Rate; Household Saving; Saving; Japan; Aging; Culture; Privater Haushalt; Sparen; Alternde Bevölkerung; Japan